2011
DOI: 10.1002/chem.201101923
|View full text |Cite
|
Sign up to set email alerts
|

Dye‐Sensitized Solar Cells Based on Donor‐π‐Acceptor Fluorescent Dyes with a Pyridine Ring as an Electron‐Withdrawing‐Injecting Anchoring Group

Abstract: A new-type of donor-acceptor π-conjugated (D-π-A) fluorescent dyes NI3-NI8 with a pyridine ring as electron-withdrawing-injecting anchoring group have been developed and their photovoltaic performances in dye-sensitized solar cells (DSSCs) are investigated. The short-circuit photocurrent densities and solar energy-to-electricity conversion yields of DSSCs based on NI3-NI8 are greater than those for the conventional D-π-A dye sensitizers NI1 and NI2 with a carboxyl group as the electron-withdrawing anchoring gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(66 citation statements)
references
References 33 publications
6
60
0
Order By: Relevance
“…Dye-sensitized solar cells (DSSCs) are one of their main applications nowadays, which have attracted a lot of interest, as a new option in photovoltaics area (especially as potential materials for photovoltaic cells) [21][22][23][24][25]. Dye-sensitized solar cells are more suitable to be used at large scale in comparison with the classical Step 2…”
Section: Introductionmentioning
confidence: 99%
“…Dye-sensitized solar cells (DSSCs) are one of their main applications nowadays, which have attracted a lot of interest, as a new option in photovoltaics area (especially as potential materials for photovoltaic cells) [21][22][23][24][25]. Dye-sensitized solar cells are more suitable to be used at large scale in comparison with the classical Step 2…”
Section: Introductionmentioning
confidence: 99%
“…Pyridine-containing D-A-type compounds have been recently studied as sensitizing dyes for DSSC. 25 In this case, pyridine functions not only as an acceptor unit but also as an anchoring unit that can coordinate with Lewis acid sites of TiO 2 to attach the dye to the TiO 2 surface; this pyridine-Ti anchor is known to facilitate electron injection from the photo-excited dye, compared with the conventional ester anchor. Based on this property, we applied the pDTSTPyT and pDTSPy polymers to DSSC.…”
Section: Applications To Opvmentioning
confidence: 99%
“…72,73 Thus, as a new type of D³A dye sensitizers for DSSCs, we have designed and synthesized novel fluorescent dyes NI3NI6 with a pyridine ring as electron-withdrawinginjecting anchoring group (Scheme 3). We demonstrated that the formation of coordinate bonds between the pyridine ring of dyes NI3NI6 and the Lewis acid sites (exposed Ti n+ cations) of the TiO 2 surface leads to efficient electron injection owing to the excellent electron communication between them, rather than the formation of a bidentate bridging linkage between the conventional D³A dye sensitizers NI1 and NI2 and the Brønsted acid sites (surface-bound hydroxy groups) of the TiO 2 surface.…”
Section: ç New Type Of D-π-a Fluorescent Dyes With Pyridine Ring As Ementioning
confidence: 99%